THE INFLUENCE OF INCOME, PREMIUMS, AND BRAND IMAGE ON THE DECISION TO USE INSURANCE SERVICES AT PT PANIN DAI ICHI LIFE SALES OFFICE MEDAN - Lidia Purba; Rifqah Harahap; Siti Junaidah (Manajemen: Jurnal Ekonomi, 2025)
The problem in this study is the fluctuation in the number of customers, where middle-income groups feel their financial burden increases after paying premiums, premiums are considered too expensive for those with limited income, and many claims are difficult to disburse. The purpose of this study is to analyze the influence of income, premiums, and brand image on the decision to use insurance services at PT Panin Dai-ichi Life Sales Office Medan. This research employs a quantitative approach with a population of 374 customers and a sample of 79, selected through incidental sampling. Data sources consist of both primary and secondary data, analyzed using multiple linear regression with SPSS version 22. The regression model obtained is: Y = 4.657 + 0.001X₁ + 0.335X₂ + 0.489X₃ + e. The results show that income, premiums, and brand image positively and significantly influence the decision to use insurance services, both partially and simultaneously. The t-test results indicate significant effects for income (t = 3.009 > 1.922), premium (t = 2.471 > 1.922), and brand image (t = 5.544 > 1.922). Simultaneously, the F-test value of 21.954 > 2.727 indicates a significant joint effect. The coefficient of determination (Adjusted R²) is 44.6%, meaning that the three variables explain 44.6% of the decision-making process to use insurance services, while the remaining 55.4% is influenced by other factors not included in this model